Epidemiologic Study of Transfusion-Related Alpha-Gal Syndrome - Richard M. Kaufman; Anne G. Hoen; Jenna Khan; C. Michael Knudson; Ryan A. Metcalf; Andres E. Mindiola Romero; Allison Mo; Richard Schäfer; Minoko Takanashi; Nancy M. Dunbar; Rebecca Cardigan; Simon J. Stanworth; et al. (JAMA Internal Medicine, 2026)
Importance Recent case reports suggest that B antigen–containing blood products may be associated with anaphylactic transfusion reactions in recipients with preformed immunoglobulin E to galactose- α -1,3-galactose (alpha-gal). Objective To test the association of local alpha-gal syndrome (AGS) prevalence and allergic transfusion reaction (ATR) in patients with blood type O. Design, Setting, and Participants In this international, multicenter, retrospective cohort study at academic medical centers, sites were assigned to AGS high- or low-prevalence clusters based on the known geographic distribution of AGS. Data were collected on platelet or plasma transfusions and ATRs during 2020 to 2024. Consecutive patients receiving platelet or plasma transfusions were included. Exposures Patients with blood type O who received B or AB units and patients with blood type O who received O units (reference group) in AGS high- and low-prevalence clusters were compared. Main Outcomes and Measures Before data collection, the hypothesis was that if transfusion-related alpha-gal syndrome (TRAGS) is a true clinical entity, excess ATRs to group B or AB units would be detected in AGS high-prevalence regions exclusively. The main measure was the overall risk ratio (RR) for ATRs to B or AB plasma or platelets in AGS high- vs low-prevalence clusters. Results In total, 558 823 platelet and plasma transfusions at 40 sites in 5 countries were analyzed, of which ATRs occurred in 1744 transfusions (0.3%). In the US AGS high-prevalence cluster (9 sites), significantly more ATRs of any severity occurred among patients with blood type O who received B or AB units vs patients with blood type O who received O units (overall RR, 3.93; 95% CI, 2.96-5.21; P < .001). In contrast, in the primary analysis of the AGS low-prevalence cluster (15 sites), excess ATRs to B or AB units were not detected. In subgroup analyses among patients with blood type O receiving B units, the RR for moderate to severe ATRs was 9.14 (95% CI, 5.39-15.52; P < .001) in the AGS high-prevalence cluster vs 2.15 (95% CI, 1.34-3.47; P = .002) in the AGS low-prevalence cluster. Outside the US, a signal consistent with TRAGS was not detected. Conclusions and Relevance This cohort study provides provocative epidemiologic evidence that TRAGS may be a unique manifestation of AGS and a previously unrecognized risk associated with transfusion. In AGS high-prevalence regions, blood collectors and hospital transfusion services should consider approaches to preventing severe ATRs from B or AB plasma or platelet units.